Attaching Redox Proteins onto Electrode Surfaces by using bis‐Silane. Issue 7 (21st April 2016) - Trashin, Stanislav; de Jong, Mats; Meynen, Vera; Dewilde, Sylvia; De Wael, Karolien
Abstract: Immobilization of redox proteins on electrode surfaces is of special interest for mechanistic studies and applications, because of the well‐controlled redox state of protein molecules at a polarized electrode and fast electron‐transfer kinetics that are free from diffusion limitation. Here, bis‐organosilane [1, 2‐bis(trimethoxysilyl)ethane] was used as a fresh solution in a pH 7 phosphate buffer without the use of any organic solvent, sol‐gel, or mesoporous bulk matrix. A short aging period of 30 min before deposition on the electrodes was optimal for the immobilization of proteins. Three redox proteins (cytochrome c, neuroglobin, and GLB‐12) were confined to the gold surface of electrodes with high coverages and stabilities, indicating that the suggested technique is simple, efficient, and generic in nature. Abstract : Stay connected : bis‐Organosilane (BTMSE) is used as a fresh solution in a pH 7 phosphate buffer without the use of an organic solvent or sol‐gel preparation for the immobilization of proteins on an electrode surface. A short aging period of 30 min before deposition on the electrodes is optimal for the immobilization of the protein, leading to high coverage and excellent film stability.